Existing barriers to consumer repair of small household appliances from a product design approach: A scoping review - Rovira-Menaya, Pedro; Pina, Carmelo; Sierra-Pérez, Jorge (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Small Household Appliances (SHA) and their associated electric and electronic waste are a major concern for the EU, which is tackling this problem with an emphasis in repair as a key strategy to prolong product lifetime. The field of product design plays a fundamental role in the configuration of products to enable their future repair. Therefore, this study explores the main barriers that consumers face when trying to repair their household appliances through a literature scoping review focused on small household appliances, from the product design and the repair ecosystem aspects. This study proposes a novel classification at product system level and product-service system level barriers. The first level relates to the physical product and its repairability, while the second relates to the entire system surrounding the product and the repair experience. According to the literature, most relevant repair barriers from the product system level were ‘Understanding of product operation’ (specially ‘Product complexity’), ‘Product accessibility’ (specially ‘Difficult disassembly and reassembly’), ‘Impossibility to repair’, ‘Obsolescence’ and ‘Safety concerns’. From the product-service system level, the most relevant were ‘Economic factors’, ‘Consumer factors’ (specially ‘Lack of time’), ‘Access to information’ and ‘Lack of support by OEM’. The discussion section points out that some of these barriers may be downplayed by shifting the mindset of the SHA industry, currently focused on cost reduction, towards quality and repairability. Finally, least mentioned barriers in the literature are worth of attention and shouldn’t be forgotten, as they point to possible research gaps.